Analisis Kelayakan Finansial Usahatani Manggis (Garcinia Mongostana L) di Kecamatan Wanayasa Kabupaten Purwakarta - Alicia Nurfauzy; Kuswarini Sulandjari; I Putu Eka Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2021)
Mangosteen is a fruit native to Southeast Asia which is a national superior commodity. One of the mangosteen production centers in Indonesia is in Wanayasa District, Purwakarta Regency. The purpose of the study: to determine the cost, acceptance and financial feasibility of mangosteen farming. Quantitative research methods by conducting surveys and observations. Primary data collection by interviews and questionnaires. Research respondents: mangosteen farmers, farmer group leaders, and extension workers. Farmers' samples were taken purposively based on the age of the plant, then randomly. The results of the study: Total expenses incurred for 20 years amounted to Rp282.105.202, Revenue earned for 20 years amounted to Rp322.894.798, Revenue for 20 years amounted to Rp605.000.000; with an interest rate of 6%, per ha of land the NPV value is Rp. 96,109,082, Net B/C Ratio is 3,045, Payback Period is 8 years, and IRR is 16%. Mangosteen farming is said to be feasible. The sensitivities that occur are a 15% decrease in selling price: NPV Rp59,641,553, Net B/C Ratio 2.22, IRR 13% and Payback Period 8 years; 30% decrease in production: NPV Rp23,174,025, Net B/C 1.42, IRR 9%, Payback Period 8 years; Increase in production costs 2.27%: NPV Rp92.772.005, Net B/C Ratio 2.93, Payback Period 8 years and IRR 16%, still considered feasible.